Intra-familial violence and peer aggression among early adolescents: moderating role of school sense of belonging - Valido, Alberto (Journal of family violence, 2021)
Aggression among peers during adolescence is associated with deleterious developmental outcomes. Family violence has been strongly associated with many forms of aggression - such as verbal and physical aggression. Yet, associations between sibling and peer aggression at school and the protective role of school belonging remain understudied. Thus, the present study addresses this gap. Middle school students (N = 1611) completed self-report surveys four times across 2 years in a U.S. Midwest state. A multi-level within- and between-person longitudinal design was employed to examine associations among sibling aggression perpetration, witnessing intrafamilial violence, and verbal and physical peer aggression at school. Also, the moderating effect of school belonging between family violence and peer aggression was also investigated. Higher levels of sibling aggression were associated with higher verbal peer aggression at both within- and between-person levels. Family violence was associated with higher verbal and physical peer aggression, but only at the between-person level and not within-individuals. Higher school belonging was associated with less verbal and physical peer aggression overtime. School belonging moderated the relation between sibling aggression and verbal as well as physical aggression; higher within-person level sibling aggression was associated with lower verbal and physical aggression when students reported a strong sense of school belonging. Aggression prevention programs that focus on fostering school connectedness may mitigate the transmission of violence from home to school.